Acquisition of Australian English vocabulary via newspapers - Mohamed Ali, Haja Mohideen (2013)

(untitled)
Australian English may not have received much research interest or attention compared to standard British English or standard American English which are considered reference varieties. Geographically the ASEAN region is closer to Australia and the country is increasingly popular with students fro overseas due to multiculturalism, world class educational institutions and its proximity to countries in Southeast Asia. It is the nearest developed country where English is used as the primary language. This paper focuses on Australian English vocabulary. The data was collected from three newspapers during a week long period.